STUDI WAKTU PERJALANAN DAN TUNDAAN DENGAN APLIKASI VISSIM PADA RUAS JALAN A.H. NASUTION - Mangaramot Justisiano Pakpahan; Budi Hartanto Susilo (Universitas Kristen Maranatha, 2021)
A.H Nasution Street is one of the primary arterial roads that connect between Cileunyi to East Bandung. East Bandung region is one of the areas that chosen by people at Bandung to settle. Therefore during rush hour there is congestion at A.H Nasution Street. The goal of this research is to identify vehicle travel time on A.H Nasution Street, and evaluate each intersection that is one of the major delays on A.H Nasution Street and provide alternative solutions using PTV Vissim. The road sections that reviewed ini this research started from the A.H nasution – Ahmad Yani Intersection until Ditbintekjatan, (Direktorat Bina Teknik Jalan dan Jembatan) with data collection time on Monday, 9th Mar 2020 at 06.00 am – 07.00 am. The existing analysis on A.H Nasution street from West to East has LoS F with vehicle travel time taken for 22 minutes 10 seconds with a delay of 410 seconds, while from East to West has LoS F with vehicle travel time taken for 23 minutes 47 seconds with a delay of 345 seconds. If repairs are made by widening the lane at Sta (0+000) – Sta (0+500) and the the prohibition of turning right at each unsignalized intersection on the section that reviewed, the A.H Nasution street from West to East has a LoS C with vehicle travel time faster with a shorter delay, while from East to West has a LoS D with vehicle travel time faster with a shorter delay.